The Existence Of Palm Oil Middlemen (Tengkulak) And Its Impact On The Presence Of Palm Oil Weighing Scales - Anggara, Agil; Soleh, Ahmad; Febliansa, Muhammad Rahman (Jurnal Fokus Manajemen, 2025)
The palm oil plantation sector plays a significant role in Indonesia's economy; however, issues such as price discrepancies and illegal trade often arise. One common phenomenon is the role of middlemen, or "toke sawit," in the palm oil supply chain. This study aims to examine the existence of palm oil middlemen (toke sawit) in relation to the introduction of palm oil weighing ramps and its impact on farmers and the palm oil industry in general. The research employs a qualitative approach, utilizing literature review and field observation to understand the relationship between the role of middlemen and their influence on the marketing system as well as transparency in palm oil weighing practices. The results show that the presence of weighing ramps can reduce farmers' dependency on middlemen, enhance price transparency, and promote fairer trade. However, on the other hand, this practice does not entirely eliminate the role of middlemen, who remain crucial in connecting farmers with large companies.